2021
DOI: 10.1136/neurintsurg-2021-017365
|View full text |Cite
|
Sign up to set email alerts
|

Impact of RapidAI mobile application on treatment times in patients with large vessel occlusion

Abstract: BackgroundCurrent efforts to reduce door to groin puncture time (DGPT) aim to optimize clinical outcomes in stroke patients with large vessel occlusions (LVOs). The RapidAI mobile application (Rapid Mobile App) provides quick access to perfusion and vessel imaging in patients with LVOs. We hypothesize that utilization of RapidAI mobile application can significantly reduce treatment times in stroke care by accelerating the process of mobilizing stroke clinicians and interventionalists.MethodsWe analyzed patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 20 publications
0
42
3
Order By: Relevance
“…One limitation of this study is that we did not evaluate the impact of these tools on clinical outcomes. Other studies have previously shown a significant improvement in transfer times of LVO patients (10), but there are mixed results at comprehensive stroke centers (9,(11)(12)(13). This study included a relatively small sample size at a single institution which may limit generalizability.…”
Section: Discussionmentioning
confidence: 94%
“…One limitation of this study is that we did not evaluate the impact of these tools on clinical outcomes. Other studies have previously shown a significant improvement in transfer times of LVO patients (10), but there are mixed results at comprehensive stroke centers (9,(11)(12)(13). This study included a relatively small sample size at a single institution which may limit generalizability.…”
Section: Discussionmentioning
confidence: 94%
“… 31 Another innovative development has been the use of the mobile application RapidAI, which analyzes the imaging of patients to detect LVOs and results in significantly lower DTP times. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, the latest generation of software has been tested to quantitatively determine ASPECTS and infarct volumes 55 56. However, based on recent publications which showed that more simplified methods to triage late window patients for EVT might be as accurate as advanced imaging,57–59 it is reasonable to suggest that incorporating FPCT not only optimizes patient selection in the early window but may also expand DTAS strategy to late window patients at centers where FP technology is available.…”
Section: Discussionmentioning
confidence: 99%